1998
DOI: 10.1107/s0108768197008963
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and Electron Diffraction Study of MgO

Abstract: Precise X-ray and high-energy transmission electron diffraction methods were used for the study of electron density and electrostatic potential in MgO crystals. The structure amplitudes were determined and their accuracy estimated using ab initio Hartree-Fock structure amplitudes as criteria. The electrostatic potential distributions, reconstructed using Fourier series from both X-ray and electron diffraction data, are in satisfactory mutual agreement and are similar to the theory. They, however, suffer from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…§ Independent atomic model. ¶ Abramov, Avilov, Belokoneva, Kitaneh, Feil, Tsirelson & Okamura (1995);Tsirelson, Avilov, Abramov, Belokoneva, Kitaneh & Feil (1997). ** Independent ionic model.…”
Section: Some Experimental Results and Discussionmentioning
confidence: 99%
“…§ Independent atomic model. ¶ Abramov, Avilov, Belokoneva, Kitaneh, Feil, Tsirelson & Okamura (1995);Tsirelson, Avilov, Abramov, Belokoneva, Kitaneh & Feil (1997). ** Independent ionic model.…”
Section: Some Experimental Results and Discussionmentioning
confidence: 99%
“…Tsirelson et al [57] used the K model to describe the ED distribution in MgO. Interionic charge transfer was found, resulting in ionic charges of AE1:36e.…”
Section: Alkaline-earth Seriesmentioning
confidence: 99%
“…B=ICP nn and B=L correlations have been established for the following electronic configurations 3d 3 , 3d 7 tetrahedral and 3d 8 [168]. Menil [169] has shown that most of the 57 Fe Mössbauer isomer shifts in (FeO n ) and (FeF n ) polyhedra can be interpreted with the help of the concept of the inductive effect of the competing bond. This study has been completed for iron(III) compounds by associating optical data, Mössbauer isomer shifts with structural and magnetical data (Tab.…”
Section: Ionic Charges Derived From Ligand Filled Spectroscopymentioning
confidence: 99%
“…8 Close inspection of the fine structure of the {101}-LSMO-poles (see inset in Fig. 2(a)) reveals that each pole is associated to four satellites lying along the [110] and [1][2][3][4][5][6][7][8][9][10] directions, indicating the occurrence of four additional orientation domains related to the precise cube-on-cube orientation by 2 to 5 tilts about the [110] and [1][2][3][4][5][6][7][8][9][10] axes. In order to determine the average in-plane strain state of the nanodots ensemble, we conducted XRD / -2h/x space mapping (/ is the azimuthal orientation) at a grazing incidence angle of 0.…”
mentioning
confidence: 99%